(untitled) (World Bulletin of Social Sciences, 2024)
In the article, the problems of artistic image and artistic portrait are discussed using the example of the novel "Makhtumkuli" by K. Muhammadrizo. As a result, the importance of static portrait, a type of artistic portrait used in the novel, and its role in creating historical figures and prototype images is determined